Swiss annuities and life insurance secure returns, asset protection, and privacy - Commercial law; Mata, Mario A. 1954- (John Wiley & Sons, 2008)
A detailed look at one of today's most secure ways to invest and protect assets. Swiss Annuities and Life Insurance covers all the important investment and legal aspects of the field. Readers will learn about the key characteristics of Swiss annuities